Economic, social and cultural human rights in the context of preventing the spread of COVID-19 in Ukraine - O. I. Zozulia (Law and Safety)
Anti-epidemic measures introduced in Ukraine to prevent the spread of COVID-19 include significant (though often implicit) restrictions on the implementation of economic, social and cultural human rights, where the issues of reasonableness and legitimacy require particular attention, when the state of emergency in Ukraine is not announced. Dialectical, formal and legal, comparative and legal, system and structural, logical and semantic and other methods of scientific cognition have been used to solve the set tasks. Theoretical provisions and legal principles of introducing and realizing guarantees and restrictions of economic, social and cultural human rights (rights to health care, safe working conditions, business activity, equal access to public service, education, sufficient standard of living, social protection, etc.) have been analyzed. in terms of preventing the spread of COVID-19 in Ukraine. The nature and features of the established anti-epidemic measures have been characterized.